Emma Sherrets: capstone - Sherrets, Emma, artist (Colorado State University. Libraries, 2024)
The artist's statement: My work as a graphic designer highlights the interplay between the user or viewer and the object which I have designed. The end goal of all of my work is to create something which communicates a message efficiently and effectively, but does so in a way that stands out to the audience. The interplay of typography, color, layout, and many other aspects are the building blocks which I use to blend creativity with purpose. I design to create community and to create change. The process of design is what excites me, I enjoy discovering which interplay of elements allows for the best interaction between the design and the viewer. Ultimately, my goal as a graphic designer is to forge connections between ideas, between brands and their audiences, and between myself and the viewer. Through my designs, I work to create experiences that are not only visually stunning but also create lasting connections between the client and the consumer.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design